2010
DOI: 10.1016/j.ajhg.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Severe X-Linked Mitochondrial Encephalomyopathy Associated with a Mutation in Apoptosis-Inducing Factor

Abstract: We investigated two male infant patients who were given a diagnosis of progressive mitochondrial encephalomyopathy on the basis of clinical, biochemical, and morphological features. These patients were born from monozygotic twin sisters and unrelated fathers, suggesting an X-linked trait. Fibroblasts from both showed reduction of respiratory chain (RC) cIII and cIV, but not of cI activities. We found a disease-segregating mutation in the X-linked AIFM1 gene, encoding the Apoptosis-Inducing Factor (AIF) mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
206
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 196 publications
(217 citation statements)
references
References 27 publications
10
206
0
1
Order By: Relevance
“…However, the effects may be tissue specific, since previous studies have observed a variable impact of AIF mutations on complex I activity (15,47), including the finding that decreasing AIF did not change complex I assembly, supercomplex formation, or activity. However, recently, a study (48) of two related patients with loss-offunction mutations in AIFM1, which affected both redox and DNA-binding properties of the AIF protein, showed no evidence of complex I deficiency in mitochondria taken from their skin fibroblasts or skeletal muscle biopsy samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects may be tissue specific, since previous studies have observed a variable impact of AIF mutations on complex I activity (15,47), including the finding that decreasing AIF did not change complex I assembly, supercomplex formation, or activity. However, recently, a study (48) of two related patients with loss-offunction mutations in AIFM1, which affected both redox and DNA-binding properties of the AIF protein, showed no evidence of complex I deficiency in mitochondria taken from their skin fibroblasts or skeletal muscle biopsy samples.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, AIF deletion impairs the function of the respiratory chain via its role on maintaining mitochondrial morphology (8). Consequently, patients affected by a mitochondrial encephalopathy linked to an AIF mutation exhibit abnormal mitochondria (30).…”
Section: Vital Function Of Aifmentioning
confidence: 99%
“…2 All other proteins contributing to OXPHOS function are autosomally encoded, therefore defects can occur within nuclear or mitochondrial-encoded genes. Mitochondrial disease is genetically and clinically heterogeneous, and can follow mendelian or X-linked inheritance patterns, or be strictly matrilineal in the case of mtDNA mutations; [3][4][5] clinical presentations range from isolated organ involvement (deafness, diabetes and cardiomyopathy) to multisystem, syndromic presentations dominated by muscle and CNS involvement. 6,7 Such heterogeneity can mean that identifying the causative genetic defect is problematic.…”
Section: Introductionmentioning
confidence: 99%